Biotransformation, Pharmacokinetics, and Pharmacological Activities of Ginsenoside Rd Against Multiple Diseases - Li, Jing; Huang, Qingxia; Yao, Yao; Ji, Peng; Mingyao, E.; Chen, Jinjin; Zhang, Zepeng; Qi, Hongyu; Liu, Jiaqi; Chen, Zhaoqiang; Zhao, Daqing; Zhou, Lei; et al. (Frontiers in Pharmacology, 2022)
Panax ginseng has a history of more than 4000 years and is widely used in Asian countries. Modern pharmacological studies have proved that ginsenosides and their compounds have a variety of significant biological activities on specific diseases inclusive of neurodegenerative diseases, certain types of cancer, gastrointestinal disease, and metabolic diseases, in which most of the interest has focused on ginsenoside Rd. Evidentiary basis showed that ginsenoside Rd ameliorates ischemic stroke, nerve injury, cancer, and other disease through involved in apoptosis, inflammation, oxidative stress, mitochondrial damage, and autophagy. In this review, we summarized the available reports on the molecular biological mechanisms of ginsenoside Rd in neurological diseases, cancer, metabolic diseases and other diseases. We also discussed the main biotransformation pathways of ginsenoside Rd obtained by fermentation.